PENGARUH STAKEHOLDER ENGAGEMENT, SOCIAL MAPPING DAN PENERAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP KETERCAPAIAN SOCIAL LICENSE TO OPERATE) - Hendra Hendra; Ike Kusdyah Rachmawati (Jurnal Ilmiah Global Education, 2023)
This study intends to analyze the effect of stakeholder engagement, social mapping and the implementation of Corporate social responsibility on the achievement of a social license to operate at PT Semen Gresik Rembang Factory. This study used a sampling technique by taking purposive sampling as a sample. The instrument for taking the questionnaire was for 355 respondents, namely the people who are in the environment of PT Semen Gresik Rembang Factory. The research data was processed as a quantitative description using path analysis techniques using application software and supported by primary data using a questionnaire. The results of this study indicate that: (1) Stakeholder engagement has a significant effect on the achievement of a social license to operate; (2) Social mapping has a significant effect on achieving a social license to operate; (3) corporate social responsibility has a significant effect on the achievement of a social license to operate; (4) Stakeholder engagement, social mapping and corporate social responsibility simultaneously influence the achievement of a social license to operate.